(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Marine polysaccharides remain an untapped reservoir for development of novel biomaterials. Algae derived sulfated polysaccharides (SPs) have their interesting pharmaceutical and biological properties. Degree and pattern ofÂ sulfation of such biopolymers favors their binding property with tissues when compared with nonâ€SPs. Due to the gelÂ formation potential, hydrocolloids such as agar, carrageenan, fucoidan, and alginate are extensively studied food and nonfoodÂ applications. Degree of sulfation and favorable physical properties are essentially required for tissue engineering applications.Â Therefore, our investigation explores the structural and gelling properties of novel polysaccharide porphyran (POR) isolatedÂ from Porphyra vietnamensis by alkali hydrolysis. Percentage yield of POR was found to be 19.7%. The sulfate content of theÂ polysaccharide was 11.1% and the main sugars present were Dâ€galactose (16.1%), 3, 6â€anhydro galactose (3, 6â€AG) (10.1%)Â and 6â€Oâ€methyl Dâ€galactose (7.81%). After hydrolysis Dâ€galactose was again confirmed by paper chromatography (Rf: 0.8)Â and phenolâ€sulfuric acid method. Gelling properties, including gelling strength (241 g/cm2), gelling temperature (35.8Â°C),Â melting temperature (70.7 Â± 0.4) and apparent viscosity (56.2 Î·) were also explored. Differential scanning calorimeterÂ analysis showed purified fraction has gel melt between 70Â°C and 80Â°C and show glass transition between 35Â°C and 38Â°C.Â Viscometric analysis was examined to analyze the different behavior of SPs fraction under the influence of cationic andÂ anionic salts and polysaccharides. Molecular mass of POR was determined (16,280). SPs were characterized by FourierÂ transform infrared and nuclear magnetic resonance spectroscopy, which showed the presence of linear backbone structureÂ called as POR. The rheological behavior of POR exhibits a gelâ€like behavior close to the one observed in commercial agar. Key words: Gelling, Porphyra, porphyran, red alga, sulfated polysaccharides